Solutions of the Sitnikov's circular restricted three body problems when primaries are oblate spheroid - Thapa, RR; Hassan, MR (BIBECHANA, 2013)
The solutions of sitnikov's circular restricted three body problem has been tried to obtain by using Lindstedt poincare method if the primaries are oblate spheroid. DOI: http://dx.doi.org/10.3126/bibechana.v10i0.9340 BIBECHANA 10 (2014) 92-99